Development of a stochastic model of failure of structural materials in creep at hardening stage - Doyar, Ivan; Poshyvalov, Volodymyr (Eastern-European Journal of Enterprise Technologies, 2016)
The results of research of patterns of long-term failure of metals and alloys in isothermal creep considering all its stages are presented. The approach to prediction of long-term strength characteristics of structural materials in isothermal creep under uniaxial steady load is proposed. This approach is original in the probabilistic interpretation of kinetic equations describing the creep, as well as a variety of failure criteria and their relative characteristics. Using the experimental creep curves, the adequate stochastic model was constructed and the method of identification of unknown constants of the model was developed. The calculations of basic probability characteristics of the time to failure on the example of experimental data for PA6 aluminum alloy specimens at various stress and temperatures levels were carried out. According to the research, it is enough to use the quadratic dependencies as dependencies of distribution parameters of random variables a and b, as well as the parameters c and g on the stress and temperature. The choice of the type of dependencies of higher degrees has little impact on calculation results. The proposed model can be used for prediction of the time to failure of various structural materials, as well as the development of methods, standards and guidelines in the field of reliability and durability assessment of structural materials.